Selection of Flour Suppliers as the Main Ingredient of Onion Crackers Using the Interpretive Structural Modeling Method and Simple Multi-Attribute Rating Technique - Adli Ghallib; Fitriani Surayya Lubis; Anwardi Anwardi; Harpito Harpito; Melfa Yola Melfa Yola (Publikasi Indonesia, 2024)
Raw materials are very important because raw materials are something that will determine whether the products produced are good and by the wishes of consumers or not, so it is necessary to pay attention to the provider of raw materials, namely the supplier of raw materials. The purpose of this research is to be able to find out the best suppliers by relying on the criteria that are the key criteria. In this study, the Interpretive Structural Modeling (ISM) and Simple Multi-Attribute Rating Technique (SMART) methods were used. The ISM method is useful for sorting out the criteria used so that it is obtained only in the form of key criteria while the SMART method is useful for determining the best supplier based on the existing key criteria. The results of this study are obtained from 9 key criteria out of 12 criteria used, namely quality criteria, delivery of goods, price of goods, communication system, control in operation, service improvement, attitude, packaging ability, and geographical location. The supplier that has the highest criteria based on the key criteria used is Sinar Terang supplier with a score of 0.5895 followed by Cece (0.555), Av (0.555), Aroma (0.5305), Harapan (0.5155), and finally Laris (0.4005).